Race and culture in New Orleans stories : Kate Chopin, Grace King, Alice Dunbar-Nelson, and George Washington Cable - Nagel, James (University Alabama Press, 2014)
"Race and Culture in New Orleans Stories posits that the Crescent City and the surrounding Louisiana bayous were a logical setting for the literary exploration of crucial social problems in America. Race and Culture in New Orleans Stories is a study of four volumes of interrelated short stories set in New Orleans and the surrounding Louisiana bayous: Kate Chopin's Bayou Folk; George Washington Cable's Old Creole Days; Grace King's Balcony Stories; and Alice Dunbar-Nelson's The Goodness of St. Rocque and Other Stories. James Nagel argues that the conflicts and themes in these stories cannot be understood without a knowledge of the unique historical context of the founding of Louisiana, its four decades of rule by the Spanish, the Louisiana Purchase and the resulting cultural transformations across the region, Napoleonic law, the Code Noir, the plaçage tradition, the immigration of various ethnic and natural groups into the city, and the effects of the Civil War and Reconstruction. All of these historical factors energize and enrich the fiction of this important region. The literary context of these volumes is also central to understanding their place in literary history. They are short-story cycles--collections of short fiction that contain unifying settings, recurring characters or character types, and central themes and motifs. They are also examples of the "local color" tradition in fiction, a movement that has been much misunderstood. Nagel maintains that "local color" literature was meant to be the highest form of American writing, not the lowest, and its objective was to capture the locations, folkways, values, dialects, conflicts, and ways of life in the various regions of the country in order to show that the lives of common citizens were sufficiently important to be the subject of serious literature. Finally, Nagel shows that New Orleans provided a profoundly rich and complex setting for the literary exploration of some of the most crucial social problems in America, including racial stratification, social caste, economic exploitation, and gender roles, all of which were undergoing rapid transformation at the end of the nineteenth century and the beginning of the twentieth"--